Historical Review of The Origin of Pancasila as A Philosophical Basis for The Implementation of Pancasila Economic System - P. Setia Lenggono (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
The economic system is very important for a nation because it has two main functions, namely a guide to directing the economy and coordinating various economic activities carried out by economic actors with different preferences. This paper presents the Pancasila Economic System (read: SEP) as an economic system structured as a joint effort based on the principle of kinship. An important foundation in regulating and managing the national economy as mandated by the 1945 Constitution. By conducting a historical and philosophical review of the origins (ontology) of Pancasila which is the basis for thinking in formulating the epistemological and axiological foundations that should be the basis for implementing national economic development, this paper reveals that SEP is a “own system” that is uniquely Indonesian. A consensus from the founders of the state in realizing the ideals of independence, in order to create the greatest possible prosperity with all the people.